Regulatory roles of 24-epibrassinolide in tolerance of Acacia gerrardii Benth to salt stress. Issue 1 (1st January 2018) - Abd_Allah, Elsayed Fathi; Alqarawi, A. A.; Hashem, Abeer; Wirth, Stephan; Egamberdieva, Dilfuza
ABSTRACT: This experiment aimed to investigate the role of 24-epibrassinolide (EBL) against NaCl − induced salinity stress in Acacia gerrardii Benth. NaCl (200 mM) imparted deleterious effects on the growth and chlorophyll contents of A. gerrardii, but foliar application of EBL (1.0 mg/l; each plant received 2.5 ml) mitigated the negative effect considerably. NaCl reduced chlorophyll content but this was significantly ameliorated by the application of EBL. EBL reduced significantly NaCl − induced oxidative stress hence protect membranes and also improved the relative water content significantly by 6.6% as compared with control. Nitrate reductase activity declined after NaCl treatment but EBL application sustained its activity under normal and stressed conditions. Exogenous application of EBL significantly improved the activity of superoxide dismutase, catalase and the enzymes of the ascorbate-glutathione pathway thereby protecting the photosynthetic electron transport chain and other metabolic processes in A. gerrardii from NaCl − induced oxidative stress.